Characterization and Antioxidant Potential of Acacia nilotica Synthesized Callus and Seed Nanoparticles - Ibe, Ifeanyi Jude; Zailani, Hauwa Ahmed; Dahiru, Mubarak Muhammad; Gali, Ishaku Adamu (Faculty of Pharmacy, Universitas Gadjah Mada, 2024)
This research aimed to explore the callogenesis, characterization, and antioxidant potential of Acacia nilotica callus and seed silver nanoparticles. The callus induction was accomplished using plant growth hormones. The silver nanoparticles (AgNPs) were synthesized from the seed and callus extracts and characterized using Gas chromatography-mass spectroscopy (GC-MS), X-ray diffraction (XRD), and Scanning electron microscopy (SEM). The antioxidant activities were evaluated by 1, 1-diphenyl-2-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP) assays, molecular docking, and molecular dynamics simulations. The callus formation ranged from 77% to 100%. The AgNPs exhibited a face-centered cubic structure with the size predicted to be 25 nm while the SEM images showed the AgNPs had clustered topography and variable surface morphology. Exactly 33 and 26 compounds were respectively identified in the callus and seed with 8-Hexadecenal 14-methyl- (Z)- (7.71%) and linoleic acid (15.77%) being the most abundant, respectively. A significantly (p < 0.05) higher DPPH and FRAP activities were demonstrated by the callus at the highest dose (1 mg/ml). Moreover, 22-Stigmasten-3-one and 3-(azepan-1-yl)-1,2-benzothiazole 1,1-dioxide, respectively from the callus and seed exhibited the most favorable docking interactions with xanthine oxidase, cytochrome P450 21A2, and myeloperoxidase with a possible activity disruption. Conclusively, the callogenesis technique might be regarded as a reliable alternative to produce pharmacologically active secondary metabolites and nanoparticles against oxidative stress-linked ailments. Moreover, 22-Stigmasten-3-one and 3-(azepan-1-yl)-1,2-benzothiazole 1,1-dioxide might be good starting materials for novel therapeutics synthesis against oxidative stress.